Utilization of Carbon-Embedded Photocatalysts Prepared at Different Oxidation Conditions for Gaseous Methyl Tertiary-butyl ether Decomposition - Lee, Jun-Yeop; Jo, Wan-Kuen (Asian Journal of Chemistry, 2013)
The present study investigated the surface and morphological characteristics and the photocatalytic activities of carbon-embedded photocatalysts for the purification of in-vehicle level methyl tertiary-butyl ether under different experimental conditions. This decomposition was achieved using titanium carbide (TiC) and five photocatalysts prepared by oxidizing TiC at different oxidation temperatures (250, 300, 350, 400 and 450 ºC, which were designated as TiC-250, TiC-300, TiC-350, TiC-400 and TiC-450, respectively). Their characteristics were determined using a variety of spectral instruments. The surface area, pore volume and carbon content of pure TiC and as-prepared photocatalysts were also determined. For the pure TiC and TiC-250, the photocatalytic decomposition for methyl tertiary-butyl ether was close to zero, whereas the other photocatalysts revealed certain degrees of photocatalytic decomposition efficiency. XRD pattern exhibited that TiO2 crystal phases were not formed for the TiC and TiC-250, indicating that these two types of powders could not have any photocatalytic functions for methyl tertiary-butyl ether decomposition. TiC-300 showed the highest methyl tertiary-butyl ether decomposition efficiency (average value of 82 %), followed by TiC-350 (average value of 77 %), TiC-400 (average value of 44 %) and TiC-450 (average value of 8 %). Consequently, the as-prepared photocatalysts could effectively be applied for airborne methyl tertiary-butyl ether purification inside vehicles, when their preparation conditions were optimized.